Austria : 2011 Article IV Consultation: Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Austria. (IMF Staff Country Reports; Country Report ;, 2011)
Increasing integration to the East has benefited the Austrian economy, but also created vulnerabilities that came to a head with the global financial crisis. The crisis has highlighted old challenges and created new ones that need to be addressed. The banking sector's return to more normal levels of profitability creates the conditions for a further build-up of high-quality capital and exit from government support. Policies to foster labor market participation by low-skill workers and human capital accumulation would increase long-term growth.